CP-008 Patient-specific medication management – An interdisciplinary challenge. (24th February 2014) - Andersen, MB; Johansen, SH; Jensen, MK; Nørregaard, LJ; Olsson, SD; Palm, H
Abstract : Background: Patient-specific clinical pharmacy services practiced in Danish hospitals have developed rapidly over the past decade. With respect to tailoring the services to need and cost this study has focused on the further use of pharmaconomists in selected steps in the medication management process freeing up pharmacist time for other input in the medication management process. Pharmaconomists are a pharmaceutical professional group in Denmark with a three year higher tertiary education (non-academic). Purpose: To improve the overall quality of the medication process without incurring additional cost by implementing a pharmaconomists service on a ward. Materials and methods: The model was tested on 200 consecutive hip fracture patients (78% female, mean age 79 (range 22–97)) from September 2012 to March 2013. Both before and during the project period, the pharmaconomists were trained in recording secondary medication history, medicines reconciliation, dispensing and administration of oral medicines and medicines at discharge. The training was performed via guided learning programmes, peer-to-peer training and structured reviews of regional medicines guidelines. Only corrections accepted by medical doctors were recorded as errors. Results: On average, the pharmaconomist used three hours daily on dispensing morning and noon medicines for 22 patients. The secondary medication history took on average 35 min per patient to complete. Each patient used an average of six different types of medicine with average of two errors in the primary medication history (total: 413 errors). The discharge process was more complex and non-standardised than expected, so pharmaconomists still needs assistance from a pharmacist here. Conclusions: The study indicates a cost-neutral model is possible, in which pharmaconomists and pharmacists are part of a close interdisciplinary team on the ward. With the right approach and skills, the pharmaconomists are able to undertake tasks that used to be performed by pharmacists. We believe that the model improves the overall quality of the medication process and has a great potential for further optimising the patient-specific clinical pharmacy services. No conflict of interest.